Human Nature, Ritual, and History: Studies in Xunzi and Chinese Philosophy - Cua, Antonio S. (Studies in Philosophy and the History of Philosophy; Ser, 2005)
Intro -- Contents -- Preface -- Acknowledgments -- PART I. XUNZI'S MORAL PHILOSOPHY -- 1. Philosophy of Human Nature (1976) -- 2. Dimensions of Li (Propriety) (1978) -- Appendix 1-Human Relationships and the Virtues in the Liji (1979) -- Appendix 2-Moral Cultivation and Music in the Liji (1979) -- 3. Ethical Uses of the Past (1984) -- 4. The Problem of Conceptual Unity (1984) -- 5. The Unity of Virtues (1985) -- 6. The Possibility of Ethical Knowledge (1989) -- 7. The Ethical and the Religious Dimensions of Li (Propriety) (1999) -- 8. Ethical Significance of Shame: Insights of Aristotle and Xunzi (2002) -- PART II. OTHER STUDIES IN CHINESE PHILOSOPHY -- 9. Practical Causation and Confucian Ethics (1974) -- 10. Moral Theory and the Quality of Life (1978) -- 11. Confucian Vision and the Human Community (1980) -- 12. Ethical Significance of Thomé H. Fang's Philosophy (1987) -- 13. Reason and Principle in Chinese Philosophy (1995) -- 14. Emergence of the History of Chinese Philosophy (1999) -- 15. Xin (Mind/Heart) and Moral Failure: Notes on an Aspect of Mencius's Moral Psychology (1999) -- Bibliography -- Index of Names -- Index of Subjects -- Glossary.